Penanaman Karakter Peduli Sosial Bagi Mahasiswa Melalui Kegiatan Pengabdian MasyarakatDi BEM FKIP UMS Tahun 2016/ 2017 - Nafisah, Devi Adestin Wulan; , Dr. Achmad Fathoni.M.Pd (2017)
The object of this research was to describe: 1) The kinds of social service to put the character of social attention for students of BEM FKIIP UMS, 2) The supporting factor in social attention character of BEM FKIIP UMS, 3) the obstacle in social attention character of BEM FKIIP UMS, 3) The solution to taking care the obstacke in social attention character for students in social service BEM FKIIP UMS. The research was qualitative research, with a descriptive design, and phenomenology. The informants of this research was the leader of social service activity, the leader of event organizer of social service activity and the member of social service activity BEM FKIIP UMS. Technique for collecting data for this research was interview, observation, and documentation. Thrustwortines data of this research was technique triangulation and source triangulation. The analyzing data technique was interactive analysis of Miles Huberman. The result of this research were: 1) each days consists of the activity related to social attention such as planting, contest, cheap market, nobar, pengajian, and sembako. the purposes of the implementation of social service was to get the polite, social relationship, working together, care characters, 2) the supporting factors in getting the social attention character for students consists of prestige and personal character, 3) the obstacle in getting the social attention character for students consists of personal character where the students can not make a good relationship with society they will be difficult in getting the characters. Beside that the tehcnical factor such as the less in guidance, 4) the solution to handle the obsetacle of social attention character was, the students need more guidance and workshop before the activity and the students also need to get more attention from others.